Đánh giá hiệu quả ứng dụng bộ chế phẩm probiotic BIDI-AGRI và BIDI-AQUA trong nuôi tôm thẻ chân trắng thương phẩm - Linh, Lê Hồng; Thảo, Đặng Thị Phương (Tạp chí Khoa học Đại học Cần Thơ, 2024)
Whiteleg shrimp (Litopenaeus vannamei) farming is a major economic sector in many countries worldwide. Infectious diseases and environmental pollution in shrimp ponds have resulted in significant economic losses for the aquaculture industry. This study presented the effects of a BIDI-AGRI and BIDI-AQUA probiotic blend consisting of Bacillus subtilis, Bacillus tequilensis, Bacillus amilolyquefaciens, Bacillus licheniformis, Lactobacillus acidophilus, Saccharomyces cerevisiae in shrimp cultured water treatment and shrimp growth. The BIDI-AGRI and BIDI-AQUA were applied in three commercial whiteleg shrimp ponds with surface areas ranging from 700 to 1200 m² for 90 days. Results showed that compared to the control, BIDI-AGRI and BIDI-AQUA improved several water quality parameters, including H₂S, NH₃, and COD concentrations, controlled Vibrio spp. populations within acceptable limits and enhanced shrimp immunity. Furthermore, shrimp ponds treated with BIDI-AGRI and BIDI-AQUA exhibited higher growth rates and yields. Due to lower investment costs and higher revenue, shrimp ponds using BIDI-AGRI and BIDI-AQUA achieved approximately 1.6 times higher profits compared to ponds using commercially available probiotics.